2006
DOI: 10.1159/000097305
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Age Specificity of Susceptibility Genes Modulating Survival at Old Age

Abstract: Objective: We aimed to investigate the influence of the genetic variability of candidate genes on survival at old age in good health. Methods: First, on the basis of a synthetic survival curve constructed using historic mortality data taken from the Italian population from 1890 onward, we defined three age classes ranging from 18 to 106 years. Second, we assembled a multinomial logistic regression model to evaluate the effect of dichotomous variables (genotypes) on the probability to be assigned to a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 67 publications
2
35
0
Order By: Relevance
“…Finally, our finding that there were essentially no sex-related differences in the possible effect of PTK2 gene variants on EL remains to be corroborated in other cohorts. Passarino et al 48 showed that genetic factors influence survival at advanced age in a sex-specific way, with genetic variability playing a stronger role in males than in females.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our finding that there were essentially no sex-related differences in the possible effect of PTK2 gene variants on EL remains to be corroborated in other cohorts. Passarino et al 48 showed that genetic factors influence survival at advanced age in a sex-specific way, with genetic variability playing a stronger role in males than in females.…”
Section: Discussionmentioning
confidence: 99%
“…The sample study was divided into three sex-specific age classes ( the age classes of women are written in square bracket) The first age class was made by men with age <66 [<73], the second class by men with age 66-88 [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91], and the third class by men with an age >88 [>91]. These gender-specific age classes were defined according to demographic information and accounted for different survivals of men and women in Italian population (Passarino et al 2006). The study protocol was approved by the Joint Ethical Committee (JEC) University of Camerino-Azienda ASUR Marche Camerino, in accordance with the Declaration of Helsinki in its revised edition and with international and local regulatory requirements.…”
Section: Subjectsmentioning
confidence: 99%
“…Indeed, genome-wide association studies (GWAS) are at present widely used to find genetic variants contributing to variation in human lifespan (Puca et al 2001;Lunetta et al 2007;Newman et al 2010;Walter et al 2011;Deelen et al 2011;Nebel et al 2011;Malovini et al 2011). Along with GWAS, studies that consider candidate biochemical pathways consisting of many biologically related genes, and a minimal number of "tagging" SNPs that efficiently capture all the common genetic variation in the assayed genomic region, are also being routinely used (Passarino et al 2006;Nebel et al 2009;Pawlikowska et al 2009;Flachsbart et al 2010).…”
Section: Introductionmentioning
confidence: 99%